2012
DOI: 10.1016/j.jcma.2011.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of maternal group B streptococcus colonization and vertical transmission in low-risk women in a single institute

Abstract: Although the positive rate of GBS culture was lower in asymptomatic low-risk pregnant women, the possibility of vertical transmission might be high. This finding is worthy of further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 27 publications
1
18
2
Order By: Relevance
“…[15][16][17] In this study prevalence of Group-B Streptococcus colonization was found to be more in women with age greater than 30 years of age. A study from Trinidad by Orrett FA et al showed a significant trend of increasing prevalence with increasing age.…”
Section: Discussionmentioning
confidence: 85%
“…[15][16][17] In this study prevalence of Group-B Streptococcus colonization was found to be more in women with age greater than 30 years of age. A study from Trinidad by Orrett FA et al showed a significant trend of increasing prevalence with increasing age.…”
Section: Discussionmentioning
confidence: 85%
“…Maternal factors associated with early streptococcal invasive disease in neonates are delivery before 37 weeks gestation, premature rupture of membrane more than 18 hours and intrapartum fever (2). There are different reports on GBS colonization in pregnant woman from Iran (22.7%) (3) (11.2%) (4) 10.2% (5) 3% (6) and other regions such as 20% in Taiwan (7) 15.3% in Lithuania (8) and (6.2%) in China (9), this difference might be resulted from the number of partners and sexual habits in different cultures. Studies on neonatal colonization in Iran show different results.…”
Section: Introductionmentioning
confidence: 99%
“…The main site for colonization of these bacteria are rectum and the vagina. Furthermore, it has been proved that the colonization in these areas is considered as a risk factor for pregnant and newborn further infection [1]. The infection by GBS in pregnant women causes bacteremia, endometritis and chorioamnionitis.…”
mentioning
confidence: 99%